Potential Natural Inhibitors of MRSA ABC Transporters and MecA Identified Through In Silico Approaches - Benson Otarigho; Paul M. Duffin; Mofolusho O. Falade (Microorganisms, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) poses a significant clinical challenge due to its resistance to multiple antibiotics. The urgent need for new therapeutic approaches has led to the exploration of natural compounds as potential treatments, particularly those targeting the key bacterial proteins involved in antibiotic resistance. This study focused on the multidrug ABC transporter and MecA proteins, which play crucial roles in MRSA′s pathogenicity and resistance mechanisms. Using computational techniques and molecular docking methods, we assessed the interactions of 80 natural compounds with S. aureus multidrug ABC transporter SAV1866 (SAV1866) and MecA proteins. Our analysis revealed 14 compounds with robust binding to SAV1866 and one compound with a strong affinity for MecA. Notably, these compounds showed weaker affinities for the MgrA, MepR, and arlR proteins, suggesting specificity in their interactions. Among the 15 promising compounds identified, 1′,2-Binaphthalen-4-one-2′,3-dimethyl-1,8′-epoxy-1,4′,5,5′,8,8′-hexahydroxy-8-O-β-glucopyranosyl-5′-O-β-xylopyranosyl(1→6)-β-glucopyranoside; Cis-3,4-dihydrohamacanthin b; and Mamegakinone exhibited the highest binding affinities to S. aureus SAV1866. These compounds represent diverse chemical classes, including alkaloids, indole derivatives, naphthalenes, and naphthoquinones, offering a range of structural scaffolds for further drug development. Our findings provide valuable insights into potential new antibacterial agents targeting S. aureus SAV1866 and MecA proteins. These results lay the groundwork for future in vitro and in vivo studies to validate these compounds′ efficacy for combating MRSA infections, potentially leading to the development of novel therapeutic strategies against antibiotic-resistant bacteria.